Government and politics of India - "Morris-Jones, W. H." (London, 1987)
India is the world's largest democracy. This study of its political life gives an account of the structure as a whole and the working of the main institutions of government, which are presented so as to show how they continuously interact with a society which is at once deeply traditional and rapidly changing. This mutual transformation of politics and society pays attention to the role of caste, language and religious community in the formation of political identity, along with the place of patron-client relations and corruption in the actual functioning of the system. The story extends from the legacies of imperial rule and the nationalist movement through the foundational years of Nehru's rule to the critical changes of the Indira Gandhi period and is brought up to date in a new Epilogue which describes the Rajiv Gandhi phase.
Keywords: India - Politics and government